Relationship of Obstetric Complications to The Event of Maternal Mortality in Indonesia - Nova Eka Wondasari; Husaini Husaini; Mohamad Isa; Eko Suhartono; Adi Nugroho (Jurnal Berkala Kesehatan, 2024)
Maternal mortality in Indonesia is still relatively high compared to neighboring countries in ASEAN, Indonesia's position globally or regionally is the second highest MMR after Laos. Maternal death (direct obstetric death) is a direct death as a result of obstetric complications in pregnancy, childbirth and the puerperium. There were some contradictive researches about obstetric and maternal death.  Some studies related, and other did not. The objective of this study was to analyze some articles that discuss the relationship of obstetric complications toward the case of maternal mortality in Indonesia In this study, an analysis of articles regarding the relationship of obstetric complications to the incidence of maternal death in Indonesia was conducted using the meta-analysis method. Obtained 11 full (full text) research articles published online in 2015-2020, searched using the Google Scholar database, PubMed. Odds Ratio is calculated by table summary of results-model-fixed-effect, using Meta-Analysis Calculator Website Meta-mar program (Free online Meta-Analysis Service). A total of 11 articles were included in the meta-analysis showing the results of maternal deaths caused by obstetric complications OR = 3,14 (95% CI 2,354-,.199). It can be concluded that obstetric complications have a 3,14 times greater risk of maternal death.